SERANGGA-SERANGGA YANG BERASOSIASI PADA TANAMAN KACANG TANAH (ARACHIS HYPOGAEA L) DI KAMPUNG ANGGER PERMEGI DISTRIK JAGEBOB KABUPATEN MERAUKE - Jefri Sembiring; Amad Arifin; Andri Prasetia; Mariana Lusia (Musamus Journal of Agrotechnology Research, 2022)
Abstract This study aims to determine the various types of insects that exist in peanut plants (Arachis hypogaea L). The research was carried out in Angger Permegi Village and the Agrotechnology Laboratory, Faculty of Agriculture, Musamus University, Merauke from July 2020 to April 2021. Sampling was carried out using two techniques, namely using soil traps and yellow glue. The results obtained were in the Vegetative phase Absolute Density Value (KM), Relative Density (KR) (%), Absolute Frequency (FM), Relative Frequency (FR) (%) in each insect genus the highest was the Syrphidae family with the value of KM (22.67), KR (0.23), FM (0.67), FM (3.24) and FR (0.23). Meanwhile, in the generative phase, the highest absolute and relative density values ​​were in the Aphididae family with KM = 50.50 and KR = 0.12%, while the lowest was in the Gryllotalpidae family with KM = 4 and KR = 0.01%. Key words : Peanuts, Diversity of insects, Merauke